An interventional study on the influence of social and family support systems on the fertility pattern of HIV-infected women. Issue 20 (21st May 2021) - Chen, Shaoping; Ning, Yifang; Tan, Yunhuan; Lin, Xiaoli; Wang, Miao
Abstract: Objectives: This study was designed to explore the influence of social and family support system on the fertility pattern of human immunodeficiency virus (HIV)-infected women. Trial design: An interventional study including 70 participants. Methods: HIV-infected female participants treated from January 2015 to January 2019 were selected, randomly divided into 2 groups, with 35cases in each group. The experimental group was given complete social and family support, whereas the control group was given basic treatment only. Changes in fertility rate, fertility number, and fertility interval were compared between the 2 groups. We also compared the changes in the quality of life (QOL), Self-rating Anxiety Scale (SAS), and Self-rating Depression Scale (SDS) of the 2 groups of participants. Results: The fertility rate of the experimental group was 43.29%, and that of in the control group was 31.96%, and the childbearing age is mainly concentrated in the 20 to 29 years; the difference was statistically significant ( P < .05). The mean number of births in the experimental group was (1.47 ± 0.61), which was significantly higher than that of in the control group (0.63 ± 0.22), and the difference was statistically significant ( P < .05). The fertility interval of the experimental group was significantly lower than that of in the control group (2.65 ± 1.34 vs 3.77 ± 0.85), and the difference was statistically significant ( P < .05). Before the intervention, there were no significant differences in the QOL scores, SAS, and SDS scores between the experimental group and the control group ( P > 0.05). After intervention, the scores of QOL in the experimental group was significantly higher than those of in the control group (54.1 ± 1.7 vs 41.2 ± 2.5); the SAS and SDS scores of the experimental group were significantly lower than those of in the control group (39.3 ± 4.2 vs 56.1 ± 5.7; 32.2 ± 6.7 vs 51.9 ± 5.8), and the difference were statistically significant ( P < .05). Conclusions: Social and family support for female participants infected with HIV can improve the fertility rate of women to some extent, increase the number of births and shorten the interval between births, and can help relief the women's anxiety, depression, and other emotional problems, which is worthy of extensive application and promotion in the society.